Impact of Government Policy on Fisheries Production, Number of Fleet Fisheries, Investment, Fisheries Household in Batam City - Malau, Albert Gamot; Hotman, Jan (International Journal of Economics and Financial Issues, 2018)
Batam city is flanked by two countries namely Malaysia and Singapore. The population of Batam is the highest of the cities / regencies in the Riau Islands region. One source of regional income in Batam City is the Fisheries sector. Production The fisheries sector has increased from year to year. This study aims to analyze the Impact of Government Policy on Fisheries Production, Number of Fisheries Fleet, Fisheries Household (2) analyze the Impact of Government Policy on Fisheries Production, Number of Fisheries Fleet, Fisheries Household in Batam City 2000-2017. Simultaneous equation model, using Time Series data with a time span from 2000-2017. Parameter is estimated by using 2SLS (Two Stage Least Squares) method, and processing data using SAS / ETS version 6.12 computer program. Analysis is carried out to find out economic policies in 2017-2022. Model forecasting simulation is carried out to analyze the impact of Government Policy on Fisheries Production, Number of Fisheries Fleet and Fisheries Household in Batam City. The alleged result shows that the impact of Government policy on fisheries production, number of fishing fleets, number of fishery households in Batam City. The factors that influence fisheries production are fisheries sector investment and fisheries production last year. Fisheries sector technology and number of fisheries houses have a positive and significant effect on fisheries production. Increasing the number of fisheries will increase fisheries production in Batam City and have a positive and significant effect, if the number of fishing fleets in the city of Batam is increased by one unit, it will increase fisheries production by 12.56 units. Government policy by increasing the number of fleet fisher by 20 percent will result in increasing fisheries production 2.1036 percent, and increasing fisheries sector investment by 3.8970 percent. Decreasing interest rates by 5 percent will have an impact on reducing investment in the fisheries sub-sector by -0.5898 and increasing fisheries production by 2.1038 percent. Keywords: Fisheries Production, Fisheries Fleet Fishing Household, Investment. JEL Classifications: K23, E22, G23 DOI: https://doi.org/10.32479/ijefi.7281